Cholesterol lowering and mortality: the importance of considering initial level of risk. Issue 6889 (22nd May 1993) - Smith, G D; Song, F; Sheldon, T A
Abstract : OBJECTIVE–To investigate the level of risk of death from coronary heart disease above which cholesterol lowering treatment produces net benefits. DESIGN–Meta-analysis of results of randomised controlled trials of cholesterol lowering treatments. METHODS–Published and unpublished data from all identified randomised controlled trials of cholesterol lowering treatments with six months or more follow up and with at least one death were included in the meta-analysis. The analyses were stratified by the rate of death from coronary heart disease in the control arms of the trials. MAIN OUTCOME MEASURES–Death from all causes, from coronary heart disease, and from causes other than coronary heart disease. RESULTS–In the pooled analysis, net benefit in terms of total mortality from cholesterol lowering was seen only for trials including patients at very high initial risk of coronary heart disease (odds ratio 0.74; 95% confidence interval 0.60 to 0.92). In a medium risk group no net effect was seen, and in the low risk group there were adverse treatment effects (1.22; 1.06 to 1.42). In a weighted regression analysis a significant (p < 0.001) trend of increasing benefit with increasing initial risk of coronary heart disease was shown. Raised mortality from causes other than coronary heart disease was seen in trials of drug treatment (1.21; 1.05 to 1.39) but not in the trials of non-drug treatments (1.02; 0.88 to 1.19). Cumulative meta-analysis showed that these results seem to have been stable as new trials appeared. CONCLUSION–Currently evaluated cholesterol lowering drugs seem to produce mortality benefits in only a small proportion of patients at very high risk of death from coronary heart disease. Population cholesterol screening could waste resources and even result in net harm in substantial groups of patients. Overall risk of coronary heart disease should be the main focus of clinical guidelines, and a cautious approach to the use of cholesterol lowering drugs should be advocated. Future trials should aim to clarify the level of risk above which treatment is of net benefit.